Evaluating the Performance of Portland Limestone Cement in Concrete Pavement and Bridge Decks: Current Insights and Future Directions - Akerele, Daniel D.; Aguayo, Federico; Wu, Lingzi (Engineering Research: Perspectives on Recent Advances Vol. 7, 2025)
Over the years, the construction industry has heavily depended on the use of ordinary Portland cement (OPC) in diverse kinds of construction. With the rising demand for sustainable infrastructure, addressing the limitations of OPC is crucial, particularly for exposed structures such as pavements and bridge decks. Portland limestone cement (PLC) is a sustainable alternative that delivers environmental benefits and comparable performance. Previous review studies have primarily concentrated on laboratory-based assessment of PLC, providing limited insights into real-world applications. This study used a systematic review and meta-analysis with a random-effects model to evaluate PLC’s strength development, durability, and sustainability. The meta-analysis was conducted using a random-effects model. The findings indicate that PLC generally matches or surpasses OPC in terms of compressive strength, freeze–thaw resistance, and sulfate durability. However, its setting time and early-age cracking require further optimisation, especially in cold climates. Additionally, this study highlights the fire performance advantages of PLC and its enhanced chloride resistance. The most significant advantage of PLC lies in its sustainability. The reduced clinker content significantly lowers the carbon footprint associated with cement production; this is a critical factor in global efforts to mitigate climate change. The analysis identified critical research gaps, including long-term field performance and regional adaptation to extreme environmental conditions. These findings contribute to a deeper understanding of PLC’s role in sustainable construction and offer future research directions on hybrid cements and admixture compatibility. The recommended future research direction can ensure PLC becomes a key material in the global push for greener construction practices.